KMO Problem # 2

If the possible positive values of b b in the equation

a + b 3 + a b 3 = 1 , \sqrt[3]{a + \sqrt{b}} + \sqrt[3]{a - \sqrt{b}} = 1 ,

can be express in the form r n x s n y , rn^x - sn^y , for r , x , s , y , n N r, x, s, y, n \in \mathbb{N} , solve for:

r + x + s + y + n = 1 5 ( r n x s n y ) . r + x + s + y + \sum_{n = 1}^5 \left( rn^x - sn^y \right ) .


Source: First Round Question 2 from the Korean Olympiad 2000 .


The answer is 1651.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Christian Daang
Feb 13, 2017

a + b 3 + a b 3 = 1 cubing the whole expression yields: a + b + a b + 3 a 2 b 3 = 1 a 2 b 3 = 1 2 a 3 a 2 b = ( 1 2 a ) 3 27 b = a 2 ( 1 2 a ) 3 27 \sqrt[3]{a + \sqrt{b}} + \sqrt[3]{a - \sqrt{b}} = 1 \\ \text{cubing the whole expression yields: } \ a + \sqrt{b} + a - \sqrt{b} + 3 \sqrt[3]{a^2 - b} = 1 \\ \sqrt[3]{a^2 - b} = \cfrac{1-2a}{3} \\ a^2 - b = \cfrac{(1-2a)^3}{27} \\ \implies b = a^2 - \ \cfrac{(1 - 2a)^3}{27}

to be b be an integer, 1 - 2a must be in the form 3k so that, 27 ( 1 2 a ) 3 27 \ | \ (1-2a)^3 . 1 2 a = 3 k a = 1 3 k 2 1 - 2a = 3k \\ \implies a = \ \cfrac{1-3k}{2}

as 1 - 3k is always divisible by 2 for k = -(2n - 1),

a = 1 3 ( ( 2 n 1 ) ) 2 = 1 + 3 ( 2 n 1 ) 2 = 6 n 2 2 = 3 n 1 , for n > 0. b = ( 3 n 1 ) 2 ( 1 2 ( 3 n 1 ) ) 3 27 b = 9 n 2 6 n + 1 ( 3 ( 2 n 1 ) 3 ) 27 b = 9 n 2 6 n + 1 + ( 2 n 1 ) 3 = 9 n 2 6 n + 1 + 8 n 3 12 n 2 + 6 n 1 = 8 n 3 3 n 2 hence, r = 8 , x = s = 3 , y = 2. \implies a = \cfrac{1 - 3(-(2n-1))}{2} = \cfrac{1 + 3(2n-1)}{2} = \cfrac{6n - 2}{2} = 3n - 1 \hspace{0.25cm}, \text{for n > 0.} \\ \implies b = (3n - 1)^2 - \cfrac{(1 - 2(3n-1))^3}{27} \\ b = 9n^2 - 6n + 1 - \cfrac{(-3(2n - 1)^3)}{27} \\ \implies b = 9n^2 - 6n + 1 + (2n - 1)^3 = 9n^2 - 6n + 1 + 8n^3 - 12n^2 + 6n - 1 = 8n^3 - 3n^2 \\ \text{hence,} \ r = 8, x = s = 3, y = 2.

n = 1 5 ( r n x s n y ) n = 1 5 ( 8 n 3 3 n 2 ) = 1635 r + x + s + y + n = 1 5 ( r n x s n y ) = 8 + 3 + 3 + 2 + n = 1 5 ( 8 n 3 3 n 2 ) = 8 + 3 + 3 + 2 + 1635 = 1651 \sum_{n = 1}^5 \left( rn^x - sn^y \right ) \Longleftrightarrow \sum_{n = 1}^5 \left( 8n^3 - 3n^2 \right ) = 1635 \\ \begin{aligned} \therefore r + x + s + y + \sum_{n = 1}^5 \left( rn^x - sn^y \right ) & = 8 + 3 + 3 + 2 + \sum_{n = 1}^5 \left( 8n^3 - 3n^2 \right ) \\ & = 8 + 3 + 3 + 2 + 1635 \\ & = \boxed{1651} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...